Strategic And Visionary Leadership Styles In Robinson Crusoe By Daniel Defoe - Garry Iverson Brygian; Sudirman Maca; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
This study aims to find out the leadership style and individual development of Robinson Crusoe in Daniel Defoe's novel, this research is expected to be a reference for further researchers. The data source used in this research is Robinson Crusoe's Novel. In analyzing the data, the researcher used a qualitative descriptive research method. The data were obtained by using reading, note-taking, and analyzing techniques through a sociological approach to literary works and to classify the leadership styles contained in the novel, the researcher used the theory of John Adair and McClelland. The results of the research show that the leadership of Robinson Crusoe could make and execute strategies and vision well, found ideas to find plans, and created and implement Robinson Crusoe's self-development to be felt and improved. Researchers could conclude that Defoe's novel Robinson Crusoe explored how humans change from helpless creatures to leaders. The visionary leadership, it could be concluded that Robinson Crusoe was able to adapt himself as a leader who was responsible for the decisions he would carry out and Robinson Crusoe was learned to lead himself.